Gender and Ocular Manifestations of Connective Tissue Diseases and Systemic Vasculitides - Maria M. Choudhary; Rula A. Hajj-Ali; Careen Y. Lowder (Journal of Ophthalmology)
Ocular manifestations are present in many connective tissue diseases which are characterized by an immune system that is directed against self. In this paper, we review the ocular findings in various connective tissue diseases and systemic vasculitides and highlight gender differences in each disease. In rheumatoid arthritis, we find that dry eyes affect women nine times more than men. The other extra-articular manifestations of rheumatoid arthritis affect women three times more commonly than men. Systemic lupus erythematosus can involve all ocular structures and women are nine times more affected than men. Systemic sclerosis is a rare disease but, again, it is more common in women with a female to male ratio of 8 : 1. Polymyositis and dermatomyositis also affect women more commonly than men but no gender differences have been found in the incidence or disease course in the systemic vasculitides associated with antineutrophil cytoplasmic antibody such as granulomatosis with polyangiitis (GPA, formerly known as Wegener’s granulomatosis). Finally, Behcet’s disease is more common in males, and male gender is a risk factor for Behcet’s disease. There is a slight female preponderance in sarcoidosis with female gender carrying a worse prognosis in the outcome of ocular disease.